The structural econometric time series analysis approach - Zellner, Arnold; Palm, Franz C., 1948- (New York : Cambridge University Press, 2010)
This book assembles previously published texts in the theory and application of the Structural Econometric Time Series Analysis (SEMTSA) approach. It provides a timely discussion of major considerations relating to the construction of econometric models that work well to explain economic phenomena, predict future outcomes and be useful for policy-making.
Includes bibliographical references and indexes.
oif 17/09/14
Loan
Keywords: Econometric models; Time-series analysis